Lessons Learned from a Very Small Pilot Study - Sharol Jacobson; Felecia G. Wood (Rural Nurse Organization; Binghamton University, 2006)
This report describes the lessons learned from a very small (three-family, nine-person) pilot study of the feasibility of in-home educational intervention for persons with diabetes in rural African American families. Lessons learned included the need to liberalize sample criteria, appreciation of the difficulties of scheduling visits with working rural families and maintaining standard intervals between visits, documentation of the learning needs of people with prior diabetes education, realizing that Caucasian nurses were accepted into African American homes and gaining insights into communication styles, finding that children were enthusiastic participants, and that even small studies produced some diffusion beyond the participants. The families all exhibited the self-reliance considered characteristic of rural families. Investigators without experience in rural nursing or research are urged to seek consultation and to pilot their study for feasibility and logistics.